Determination and analysis of macro-featured parameters based on kilogram-level coal spontaneous combustion experiment - Xu, Yanhui (Frontiers in Materials, 2023)
The quantitative characterization of coal spontaneous combustion and the accurate determination of the dangerous degree are hot and difficult in the field of coal mine safety. In the paper, the experimental test analysis of Huangling No.2 coal was carried out by a self-designed and built kilogram-level coal spontaneous combustion experimental device, and the macro featured parameters were obtained and analyzed, such as temperature field, index gas, weight, oxygen consumption rate and exothermic intensity, and spontaneous combustion limit parameters. The results show that the experimental spontaneous combustion period of Huangling No.2 coal is 34 days. When the coal temperature was below the critical temperature of 74.59℃, the oxidation of coal samples was relatively slow, and the oxygen consumption and the production rate of gas products did not change much. After the coal temperature exceeded the critical temperature, the oxygen consumption rate and exothermic intensity increased faster and the oxidation accelerated. After reaching the dry cracking temperature of 104.93°C, the oxidation degree accelerated sharply. CO starts to appear at the beginning of the experiment, and the increase of CO gas concentration during the heating process is exponential and can be used as an index gas. Under the temperature condition of 40℃, the floating coal of 0.7m needs 25.83% oxygen concentration, and the maximum air leakage intensity of the coal is negative, and no spontaneous combustion will occur. The test data and calculation results of the experiment are important for the prediction and forecast of natural fires and the determination of the risk of spontaneous combustion on site.